In vitro safety evaluation of rare earth-lean alloys for permanent magnets manufacturing - Carlos Rumbo (Nature Portfolio, 2021)
Abstract Due to their exceptional physico-chemical and magnetic characteristics, rare earth (RE) permanent magnets are applied in multiple critical technologies. However, several environmental and economic difficulties arising from obtaining RE elements have prompted the search of alternatives with acceptable magnetic properties but containing a lower percentage of these elements in their composition. The aim of this work was to perform a preliminary toxicological evaluation of three forms of newly developed RE-lean alloys (one NdFeTi and two NdFeSi alloys) applying different in vitro assays, using as a benchmark a commercial NdFeB alloy. Thus, the effects of the direct exposure to powder suspensions and to their derived leachates were analysed in two model organisms (the A549 human cell line and the yeast Saccharomyces cerevisiae) applying both viability and oxidative stress assays. Moreover, the impact of the alloy leachates on the bioluminescence of Vibrio fischeri was also investigated. The obtained data showed that only the direct interaction of the alloys particulates with the applied organisms resulted in harmful effects, having all the alloys a comparable toxicological potential to that presented by the reference material in the conditions tested. Altogether, this study provides new insights about the safety of NdFeTi and NdFeSi alloys.